Altered spontaneous brain activity patterns in patients with unilateral acute open globe injury using amplitude of low-frequency fluctuation: a functional magnetic resonance imaging study - Tan G (Dove Medical Press, 2016)
Gang Tan,1,2,* Xin Huang,1,3,* Lei Ye,1 An-Hua Wu,2 Li-Xian He,2 Yu-Lin Zhong,1 Nan Jiang,1 Fu-Qing Zhou,4 Yi Shao1 1Department of Ophthalmology, The First Affiliated Hospital of Nanchang University, Nanchang, Jiangxi, 2Department of Ophthalmology, The First Affiliated Hospital of University of South China, Hengyang, Hunan, 3Department of Ophthalmology, The First People’s Hospital of Jiujiang City, Jiujiang, 4Department of Radiology, The First Affiliated Hospital of Nanchang University, Jiangxi Province Medical Imaging Research Institute, Nanchang, Jiangxi, People’s Republic of China *These authors contributed equally to this work Objective: The aim of this study was to evaluate altered spontaneous brain activities in patients with unilateral acute open globe injury (OGI) using amplitude of low-frequency fluctuation (ALFF) method and its relationship with their clinical manifestations.Patients and methods: A total of 18 patients with acute OGI (16 males and two females) and 18 healthy controls (HCs, 16 males and two females) closely matched in age, sex, and education were recruited in this study. The ALFF method was used to evaluate the altered spontaneous brain activities. The relationships between the mean ALFF signal values of different brain regions and the clinical features were evaluated by correlation analysis. Acute OGI patients were distinguished from HCs by receiver operating characteristic curve.Results: Compared with HCs, acute OGI patients had significantly higher ALFF values in the left cuneus, left middle cingulum cortex, and bilateral precuneus. Furthermore, the age of OGI patients showed a negative correlation with the ALFF signal value of the left middle cingulum cortex (r=-0.557, P=0.016) and a negative correlation with the mean ALFF signal value of the bilateral precuneus (r=-0.746, P<0.001). The ALFF signal value of the bilateral precuneus was negatively correlated with the duration of OGI (r=-0.493, P=0.038) and positively correlated with the vision acuity of the injured eye (r=0.583, P=0.011).Conclusion: Acute OGI mainly induces dysfunction in the left cuneus, left middle cingulum cortex, and bilateral precuneus, which may reflect the underlying pathologic mechanisms of abnormal brain activities in OGI patients. Keywords: ALFF, open globe injury, resting state, spontaneous activity, magnetic resonance imaging